Introducing auto-disable syringes to the national immunization programme in Madagascar - Drain Paul K.; Ralaivao Josoa S.; Rakotonandrasana Alexander; Carnell Mary A. (The World Health Organization, 2003)
OBJECTIVE: To evaluate the safety and coverage benefits of auto-disable (AD) syringes, weighed against the financial and logis- tical costs, and to create appropriate health policies in Madagascar. METHODS: Fifteen clinics in Madagascar, trained to use AD syringes, were randomized to implement an AD syringe only, mixed (AD syringes used only on non-routine immunization days), or sterilizable syringe only (control) programme. During a five-week period, data on administered vaccinations were collected, interviews were conducted, and observations were recorded. FINDINGS: The use of AD syringes improved coverage rates by significantly increasing the percentage of vaccines administered on non-routine immunization days (AD-only 4.3%, mixed 5.7%, control 1.1% (P<0.05)). AD-only clinics eliminated sterilization sessions for vaccinations, whereas mixed clinics reduced the number of sterilization sessions by 64%. AD syringes were five times more expensive than sterilizable syringes, which increased AD-only and mixed clinics’ projected annual injection costs by 365% and 22%, respectively. However, introducing AD syringes for all vaccinations would only increase the national immunization budget by 2%. CONCLUSION: The use of AD syringes improved vaccination coverage rates by providing ready-to-use sterile syringes on non-routine immunization days and decreasing the number of sterilization sessions, thereby improving injection safety. The mixed programme was the most beneficial approach to phasing in AD syringes and diminishing logistical complications, and it had minimal costs. AD syringes, although more expensive, can feasibly be introduced into a developing country’s immunization programme to improve vaccination safety and coverage.